Perlindungan Hukum Pencipta Lagu Rohani Yang Lagunya Digunakan Pada Peribadatan Gereja Dimedia Youtube Tanpa Izin - Intan Darmayanti; Devi Siti Hamzah Marpaung (Jurnal Ilmiah Wahana Pendidikan, 2022)
In 2019 Indonesia was hit by Covid-19 which caused many activities to be limited to crowding, both schools, offices and worship activities so that each of us is required to continue to adapt to existing conditions, one of which is worshiping by singing spiritual songs virtually. Where nowadays singing or using songs virtually can be categorized as copyright infringement, as in the case between IUP and the church regarding spiritual songs sung via youtube streaming which is considered as the use of IUP's creations and the church is obliged to pay the investment value for the song. which is used as royalty payments, in this study it is expected to be able to answer the problem with the Library method by looking at the legislation and other legal materials, so that we can answer the problem of using a work that can be categorized as a copyright infringer if it meets several elements and can be subject to royalties with the provisions which is regulated in law number 28 of 2014. So that it can create maximum legal protection for copyright.